Intergovernmental Fiscal Transfers : Principles and Practice - Boadway, Robin; Shah, Anwar (Washington, DC : World Bank, 2012)
The design of intergovernmental fiscal transfers has a strong bearing on efficiency and equity of public service provision and accountable local governance. This book provides a comprehensive one-stop window/source of materials to guide practitioners and scholars on design and worldwide practices in intergovernmental fiscal transfers and their implications for efficiency, and equity in public services provision as well as accountable governance.